Revolutionised technologies for marketing: Theoretical review with focus on artificial intelligence - Bahman Peyravi; Julija Nekrošienė; Liudmila Lobanova (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Information technology and its implications have shown significant developments in the last decades. The internet revolution and digital marketing have created a shrinking force on mass media advertising. They have formed the backbone of personalisation, marketing automation, neuromarketing, viral marketing, voice recognition, and conversion optimisation, and thus, Artificial Intelligence (AI) has risen as the phenomenon in marketing activities. Theoretical analysis of relevant researches on AI tools and future trends, presentation of conceptual framework and methodology design, and presentation of the research findings are the objectives of the research. This study has potential limitations such as the data collection process and access to the relevant literature. AI for marketing has already become a significant part of today's competitive world, which utilising the marketing opportunities to obtain business goals and create breakthrough using AI. Hence, this paper aims to illustrate the theoretical review on the nexus between AI and marketing, which would lead to understanding the future scope of AI and its penetration in marketing activities.
Keywords: O32; M31; 650; artificial intelligence; marketing; marketing automation; information technology; big data; multichannel marketing; artificial intelligence tools